Exact CT-based liver volume calculation including nonmetabolic liver tissue in three-dimensional liver reconstruction - Müller, Sascha A.; Bläuer, Karin; Kremer, Michael; Thorn, Matthias Sebastian; Mehrabi, Arianeb; Meinzer, Hans-Peter; Hinz, Ulf; Metzger, Jürg; Büchler, Markus W.; Schmied, Bruno (Journal of surgical research, 2010)
Exact preoperative determination of the liver volume is of great importance prior to hepatobiliary surgery, especially in living donated liver transplantation (LDLT) and extended hepatic resections. Modern surgery-planning systems estimate these volumes from segmented image data. In an experimental porcine study, our aim was (1) to analyze and compare three volume measurement algorithms to predict total liver volume, and (2) to determine vessel tree volumes equivalent to nonmetabolic liver tissue. Twelve porcine livers were examined using a standardized three-phase computed tomography (CT) scan and liver volume was calculated computer-assisted with the three different algorithms. After hepatectomy, livers were weighed and their vascular system plasticized followed by CT scan, CT reconstruction and re-evaluation of total liver and vessel volumes with the three different algorithms. Blood volume determined by the plasticized model was at least 1.89 times higher than calculated by multislice CT scans (9.7% versus 21.36%, P=0.028). Analysis of 3D-CT-volumetry showed good correlation between the actual and the calculated liver volume in all tested algorithms with a high significant difference in estimating the liver volume between Heymsfield versus Heidelberg (P=0.0005) and literature versus Heidelberg (P=0.0060). The Heidelberg algorithm reduced the measuring error with deviations of only 1.2%. The present results suggest a safe and highly predictable use of 3D-volumetry in liver surgery for evaluating liver volumes. With a precise algorithm, the volume of remaining liver or single segments can be evaluated exactly and potential operative risks can therefore be better calculated. To our knowledge, this study implies for the first time a blood pool, which corresponds to nonmetabolic liver tissue, of more than 20% of the whole liver volume.
Erstmals am 9. Juni 2009 online veröffentlicht
Gesehen am 11.05.2023